1986
DOI: 10.1007/bf01849300
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-pathological study of Fallopian tubes after transcervical insertion of quinacrine hydrochloride pellets

Abstract: This study lends support to others indicating the apparent safety and effectiveness of multiple transcervical insertions of quinacrine hydrochloride as pellets in 240 mg dosage to achieve permanent sterilization. In order to study the effects of the number of quinacrine pellet insertions and the site of placement of the pellets in the uterus of prehysterectomy volunteers, a scoring system of histological changes in the Fallopian tube was designed. Quinacrine pellets were deposited at the fundus using a straigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

1987
1987
1996
1996

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 6 publications
1
11
0
Order By: Relevance
“…A prehysterectomy study of Merchant and her co-workers [23] demonstrated that longer periods between quinacrine insertion and hysterectomy resulted in a higher incidence of tubal closure, and she recommended an additional contraceptive for at least six weeks post-insertion. Her study also documented a positive correlation between dose of quinacrine and efficacy, but higher doses extend tubal damage beyond the intramural segment.…”
Section: Efficacymentioning
confidence: 97%
“…A prehysterectomy study of Merchant and her co-workers [23] demonstrated that longer periods between quinacrine insertion and hysterectomy resulted in a higher incidence of tubal closure, and she recommended an additional contraceptive for at least six weeks post-insertion. Her study also documented a positive correlation between dose of quinacrine and efficacy, but higher doses extend tubal damage beyond the intramural segment.…”
Section: Efficacymentioning
confidence: 97%
“…Merchant and colleagues [18] recently found in a prehysterectomy study that greater height of the endometrium may play a protective role against the action of quinacrine.…”
Section: The Qinscrine Pellet Methodsmentioning
confidence: 97%
“…They also indicated that neither the number of insertions nor the place of deposition of the pellets (whether at the fundus or at the cornual areas) affected the degree of tubal inflammation and fibrosis [9].…”
Section: Introductionmentioning
confidence: 99%
“…Zipper and associates have observed that quinacrine has an occlusive effect on the intramural portion of the human fallopian tubes [1]. In spite of the extensive clinical studies [2][3][4][5][6] and others], histopathological research on the changes that occur when quinacrine is placed into the uterus is scarce [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation